Religiosity and mental health stigma among adults in Malaysia - Arif, Nur Syafiqa Mohd; Olagoke, Salami Mutiu (University of Muhammadiyah Malang, 2024)
This study explored religiosity's impact on mental health stigma among 451 adults of various religions in Malaysia using quantitative methods. Participants, including Muslims, Buddhists, Hindus, and Christians, completed the Centrality of Religiosity and Perceived Devaluation-Discrimination scales via an online Google form. Findings indicated high religiosity and moderate mental health stigma levels overall. Pearson correlations showed no significant relationship between religiosity and stigma across all groups. However, Buddhists demonstrated a small to moderate correlation (r = 0.27, p < 0.05) between Public Practice of religiosity and stigma, while Hindus showed a similar effect (r = 0.24, p < 0.05) with Experience of religiosity. One-way ANOVA revealed no stigma differences between religious groups. Addressing mental health stigma is crucial, given its impact on help-seeking behaviors. Future research should focus on fostering inclusive attitudes towards mental illness while respecting religious beliefs.